Revitalizing Intangible cultural heritage via derivative design: A focus on chinese woodblock printing - Shao-Feng Wang; Chun-Ching Chen (PLoS ONE, 2025)
Traditional safeguarding of intangible cultural heritage often prioritizes the preservation of craftsmanship, while allocating less attention to the innovation and activation of derivatives. This investigation extracts the identifiable intellectual property from Chinese woodblock New Year pictures, establishes a design framework to transition from two-dimensional to three-dimensional elements, and integrates generative design to examine the viability and adaptability of generative Design methods. Specifically, employing Chinese woodcut New Year pictures as a pivotal case, design constituents are elicited through interval questionnaires and on-site surveys. Subsequently, employing a comprehensive experiential approach and user journey mapping, a compendium of generative Design methods is distilled. Augmenting this, recommendations are formulated by considering generative design as a variable. Conclusively, through a dependent sample T-test, it is discerned that generative design effectively enhances both the quantity and caliber of design propositions. This inquiry dissects the plausibility of the generative Design approach for Chinese woodblock New Year pictures, extrapolating a blueprint for said derivatives and unearthing three-dimensional design concepts within the methodological framework. Ultimately, this endeavor facilitates the dynamic preservation and widespread propagation of intangible cultural heritage, concurrently bridging the chasm between planar and three-dimensional realms through innovative paradigms.